Linear-scaling self-consistent field theory based molecular dynamics: application to C60buckyballs colliding with graphite - Richters, Dorothee; Kühne, Thomas D. (Molecular Simulation, 2018)
In this work, we investigate the collision of a C60 fullerene with graphite using large-scale molecular dynamics simulations, where the interatomic forces are computed ‘on-the-fly’ by means of self-consistent tight-binding calculations. This method is based on an exact decomposition of the grand-canonical potential for independent fermions suitable for linear-scaling electronic structure calculations. We observe that at lower collision velocities, the buckyball is rebound from the graphite surface, but that starting from 50 km/s chemisorption processes are occurring that causes the buckyball to sticks to the topmost graphene layer. These outcomes are in stark contrast to previous simulations using empirical interaction potentials, but in very good agreement with experimental measurements.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Ab-initio molecular dynamics; Langevin equation; linear-scaling electronic structure methods; self-consistent tight binding